Map-based cloning of the APRR2 gene controlling green stigma in bitter gourd (Momordica charantia) - Zhan, Jinyi; Zhong, Jian; Cheng, Jiaowen; Wang, Yuhui; Hu, Kailin (Frontiers in Plant Science, 2023)
Bitter gourd is an economically important vegetable and medicinal crop distinguished by its bitter fruits. Its stigma color is widely used to assess the distinctiveness, uniformity, and stability of bitter gourd varieties. However, limited researches have been dedicated to genetic basis of its stigma color. In this study, we employed bulked segregant analysis (BSA) sequencing to identify a single dominant locus McSTC1 located on pseudochromosome 6 through genetic mapping of an F2 population (n =241) derived from the cross between green and yellow stigma parental lines. An F2-derived F3 segregation population (n = 847) was further adopted for fine mapping, which delimited the McSTC1 locus to a 13.87 kb region containing one predicted gene McAPRR2 (Mc06g1638), a homolog of the Arabidopsis two-component response regulator-like gene AtAPRR2. Sequence alignment analysis of McAPRR2 revealed that a 15 bp insertion at exon 9 results in a truncated GLK domain of its encoded protein, which existed in 19 bitter gourd varieties with yellow stigma. A genome-wide synteny search of the bitter gourd McAPRR2 genes in Cucurbitaceae family revealed its close relationship with other cucurbits APRR2 genes that are corresponding to white or light green fruit skin. Our findings provide insights into the molecular marker-assisted breeding of bitter gourd stigma color and the mechanism of gene regulation for stigma color.